(untitled) (Research, Society and Development, 2022)
Housing construction requires a large amount of natural resources, causing significant damage to the environment. This work aims to quantify the potential negative environmental impacts of the most relevant inputs used in the construction of residential buildings per m² of built area. To represent the most common constructions in Brazil, three popular standard residential projects, employed in government housing programs, with different floors and construction methods, were used as a reference for input calculations. Potential negative environmental impacts were estimated using the Life Cycle Assessment methodology. The results show that the greatest negative environmental impacts are related to buildings with more than one floor, mainly due to the use of cement and ceramic coating. Finally, this study provides information that helps decision-making, the elaboration of architectural projects, construction processes and the acquisition of construction materials, aiming to minimize potential negative environmental impacts.